Optimizing in-hospital triage for large vessel occlusion using a novel clinical scale (GAI2AA). (26th November 2019) - Ohta, Tsuyoshi; Nakahara, Ichiro; Matsumoto, Shoji; Kondo, Daisuke; Watanabe, Sadayoshi; Okada, Kenji; Fukuda, Maki; Masahira, Noritaka; Tsuno, Takaya; Matsuoka, Toshiki; Takemura, Mitsuhiro; Fukuda, Hitoshi; et al.
Abstract : Objective: To identify a proximal anterior circulation occlusion for effectively administering immediate mechanical thrombectomy by developing a novel, simple diagnostic scale to predict the occlusion, to compare its validity with available scales, and to assess its utility. Methods: To develop a novel clinical scale, we retrospectively analyzed a cohort of 429 patients with acute ischemic stroke from a single center. The novel scale GAI2 AA was applied to a prospective cohort of 259 patients from 3 stroke centers for external validation. The utility of the scale as an in-hospital triage was compared for the temporal factors of 158 patients with the occlusion. Results: In a scale-developmental phase, those with a proximal anterior circulation occlusion had significantly more frequent signs of hemispheric symptoms, including gaze palsy, aphasia, inattention, arm paresis, and atrial fibrillation. The GAI2 AA scale was developed using consolidated hemispheric symptoms and was scored as follows: score = 2, arm paresis score = 1, and atrial fibrillation score = 1. A cutoff value ≥3 was optimal for the correlation between sensitivity (88%) and specificity (81%), with a C statistic of 0.90 (95% confidence interval 0.87–0.93). External validation indicated that discrimination was significantly better than or not different from that of available complex scales. Door-to-puncture time was significantly reduced (91 [82–111] vs 52 [32–75] minutes, p < 0.001). Conclusion: The GAI2 AA scale showed high sensitivity and specificity when an optimal cutoff score was used and was useful as an in-hospital triage tool.